1992
DOI: 10.2118/21213-pa
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Massively Parallel SIMD Computer for Reservoir Simulation

Abstract: Summary Massively parallel single-instruction, multiple-data (SIMD) computers have shown much promise in solving numerically intensive problems ranging from molecular modeling to computational fluid dynamics. Much of the research on the use of parallel computing for reservoir simulation, however, has been parallel computing for reservoir simulation, however, has been limited to coarse-grain, shared memory computers or medium-grain hypercubes. We report here on research performed on a massivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…-Our method reduces runtime, yet preserves timestamp ordering and causal relationships of events. Ordinary differential equations [Franklin 1978] (2) Reservoir simulation [Rutledge et al 1991] (3)…”
Section: Parallel Simulation Problem Spacementioning
confidence: 99%
“…-Our method reduces runtime, yet preserves timestamp ordering and causal relationships of events. Ordinary differential equations [Franklin 1978] (2) Reservoir simulation [Rutledge et al 1991] (3)…”
Section: Parallel Simulation Problem Spacementioning
confidence: 99%
“…Mayer (1989) solved the Buckley-Leverett problem on a Thinking-Machines CM-2 machine and showed that the machine can handle large problems as well. Later, Rutledge et al (1991) ported a three-phase three-dimensional black-oil simulator to a parallel architecture and successfully simulated a reservoir problem with two million gridblocks. Killough and Bhogeswara (1991) The research that this report summarizes involves the application of distributedmemory computing practices on CRAY T3D and CRAY T3E.…”
Section: Parallel Computingmentioning
confidence: 99%
“…To conquer these two issues, parallel computation techniques have been involved in reservoir simulations. Since 1980s, various of parallel simulators were developed (Li et al, 1995;Wheeler and Smith, 1989;Rutledge et al, 1991;Shiralkar et al, 1997;Parashar et al, 1997;Kaarstad et al, 1995;Killough and Bhogeswara, 1991;Killough et al, 1997). In (Dogru et al, 2002(Dogru et al, , 2009), Dogru et al developed a parallel simulator, GigaPOWERS, which has been successfully applied to a case with one billion gird cells, and a truncated Neumann series preconditioner is developed.…”
Section: Introductionmentioning
confidence: 99%